A Novel Mucilage from Ficus glomerata Fruits for Transdermal Patches: Taking Indomethacin as a Model Drug: A novel mucilage from Ficus glomerata fruits - Hindustan Abdul Ahad; Chitta Suresh Kumar, Anuradha CM; Kishore Kumar Reddy; Chandra Sekhar A (Iranian Journal of Pharmaceutical Sciences, 2011)
The present study was performed to explore the matrix property of Ficus glomerata fruit mucilage for making transdermal patches. The mucilage was evaluated for its physicochemical properties. Various transdermal patches of indomethacin were prepared by solvent evaporation technique using different proportions of F. glomerata fruit mucilage. The compatibility studies between indomethacin and F. glomerata fruit mucilage revealed that there were no negative interactions between indomethacin and the mucilage. The formulated patches were evaluated for physical properties, pre-formulary, post-formulary and skin irritation characteristics and they were found satisfactory. The experimental results shows that the drug release from the patches delayed in controlled manner as the proportion of F. glomerata fruit mucilage increased. The accelerated stability studies proved that the formulated patches were stable at stressed storage conditions. It was concluded that F. glomerata fruit mucilage can be used as polymer for making transdermal patches.